High performance anode with dendritic porous structure for low temperature solid oxide fuel cells. (13th September 2018) - Shao, Xin; Rickard, William D.A.; Dong, Dehua; Dang, Huu; Saunders, Martin; Dodd, Aaron; Parkinson, Gordon; Li, Chun-Zhu
Abstract: A dendritic porous supported microstructure simultaneously creates small pore size and broad gas diffusion pathways in a solid oxide fuel cell anode membrane. This microstructure also achieves pore sizes that reduce with increasing depth within the membrane without increasing the structure tortuosity. Such a microstructure supplies high triple phase boundary density, fast gas diffusion and low polarization resistance. Here we characterise the performance of a porous anode with such a dendritic microstructure. The solid oxide fuel cell with this high performance anode achieved 0.92 W cm −2 power density at 600 °C. Highlights: A graded porous structure with natural transition and all connected pores for SOFC anode. Dendritic microstructure supplies high TPB density and fast gas diffusion simultaneously. Maximum power density of 0.92 W cm −2 at 600 °C is obtained with the dendritic anode structure and a general LSCF/GDC cathode.